Anatomical bone structure differences in patients with hemophilic arthropathy of the knee - Ekinci, Mehmet; Akgül, Turgut; Arzu, Ufuk; Bayram, Serkan; Yağcı, Taha Furkan; Kılıçoğlu, Önder (Journal of Clinical Imaging Science)
Objectives: The anatomical differences of the bony structure of the knee joint in patients with hemophilia were evaluated, and the results were compared with the knees of patients with primary gonarthrosis and no arthrosis. Material and Methods: This study reviewed 41 knees in 21 patients (with an Arnold-Hilgartner classification of Stages 4 and 5 hemophilic arthropathy) who underwent total knee arthroplasty in single center. Two control groups including 21 asymptomatic patients (42 knees) and 21 primary knee osteoarthritis patients (42 knees) were formed to compare the measurements with hemophiliacs. Femoral mediolateral width, femoral anteroposterior width, femur and tibia diaphysis width, adductor tubercle-joint line distance, tibial plateau width, and medial and lateral tibia plateau width were measured separately. Results: Femoral mediolateral width was significantly narrow comparing with healthy individuals and primary knee osteoarthritis group. Tibial plateau was similar to asymptomatic group but significantly narrow compared with primary knee osteoarthritis group. With the correlation, the tibial plateau measurements and medial and lateral plateau were significantly narrow at hemophilic arthropathy group (P < 0.05). The slope was less in hemophilic patients as compared with asymptomatic individuals (P: 0.001). Hemophilic patients had larger femoral aspect ratios than asymptomatic group but there were no observable differences with the primary osteoarthritis group. For the tibial aspect ratios, hemophilic had a smaller ratio than the primary osteoarthritis group but there were no significant differences with the asymptomatic group. Conclusion: Hemophilic knee has a mismatch between femoral and tibial side while comparing with the other groups. Level of Evidence: Level IV, cross-sectional study.